2013
DOI: 10.1210/en.2012-2206
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor in the Hypothalamus Is Sufficient to Rescue Normal Thermoregulatory Function in Male Oxytocin Receptor Knockout Mice

Abstract: Oxytocin (OXT) and OXT receptor (OXTR) have been implicated in the regulation of energy homeostasis, but the detailed mechanism is still unclear. We recently showed late-onset obesity and impaired cold-induced thermogenesis in male OXTR knockout (Oxtr(-/-)) mice. Here we demonstrate that the OXTR in the hypothalamus has important functions in thermoregulation. Male Oxtr(-/-) mice failed to maintain their body temperatures during exposure to a cold environment. Oxtr(-/-) mice also showed decreased neuronal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 54 publications
4
84
0
1
Order By: Relevance
“…In support of the former (that oxytocin in the VMN increases the thermic effect of food), it was reported that oxytocin in the DMH/VMN is essential for cold-induced thermogenesis (18). Oxytocin receptor-deficient mice have reduced ␤ 3 -adrenergic receptor expression and elevated expression of ␣ 2A -adrenergic receptor in brown adipocytes (18).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In support of the former (that oxytocin in the VMN increases the thermic effect of food), it was reported that oxytocin in the DMH/VMN is essential for cold-induced thermogenesis (18). Oxytocin receptor-deficient mice have reduced ␤ 3 -adrenergic receptor expression and elevated expression of ␣ 2A -adrenergic receptor in brown adipocytes (18).…”
Section: Discussionmentioning
confidence: 96%
“…Oxytocin receptor-deficient mice have reduced ␤ 3 -adrenergic receptor expression and elevated expression of ␣ 2A -adrenergic receptor in brown adipocytes (18). ␤ 3 -adrenergic receptor and ␣ 2A -adrenergic receptor have opposing actions in brown adipose tissue, ␤ 3 -adrenergic receptor activation increases thermogenesis, whereas ␣ 2A -adrenergic receptor activation inhibits thermogenesis (for review, see Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, oxytocin has been related to many social behaviors as in other mammals, but also more "abstract" sociality such as that found in economic trust games (Kosfeld et al, 2005;Zak et al, 2007). Recent studies have begun to reveal a direct link between OT and the other previously mentioned homeostatic processes, namely thermoregulation and metabolism (Kasahara et al, 2007(Kasahara et al, , 2013Takayanagi et al, 2008;Chaves et al, 2013). Chaves et al (2013) found support that OT has inhibitory effects on carbohydrate preferences and is associated with rectal temperatures.…”
Section: Moving To Exploration and Energeticsmentioning
confidence: 92%
“…To our knowledge, gene expression of oxytocin receptor in the hypothalamus under the conditions of chronic stress in rats or mice has not been studied thus far. Oxytocin receptors in the hypothalamus play an important role in energy homeostasis, including feeding behavior (Arletti et al 1989) and thermoregulation (Kasahara et al 2013). Oxytocin receptors are located in several hypothalamic nuclei and their roles in reproductive functions are underlined by changes in binding and/or gene expression during the estrous cycle and pregnancy (Bale et al 1995, Bealer et al 2006.…”
Section: Discussionmentioning
confidence: 99%